Constraints and Prospects of growing pulses in rice fallows of India - Kumar, Narendra; Hazra, K. K.; Singh, Saumya; Nadarajan, N. (Indian Farming, 2017)
Legumes are a natural nitrogen manufacturing factory in the fieldand growing these crops play a vital role in increasing nitrogenproduction in addition to qualifying for the demands of dietary proteinand energy. Continuous cultivation of rice in the rice fallows areas cause disturbance in the ecology of the system and compactness of the soil along with numerous biotic, abiotic and socio-economic constraints. Incorporation of legumes help in restoring soil organic matter and reducing pest and disease problems, improves sustainability.